ANALISIS KINERJA KETUA KUB DALAM MENINGKATKAN KUALITAS PELAYANAN PASTORAL DI WILAYAH V PAROKI STA. FAMILIA SIKUMANA - Ngongo, Maria Hendritha Lidya; Dhambo, Veronika Merlina (STIPAS Keuskupan Agung Kupang, 2024)
Pastoral care is an important aspect of church life to accompany people on their journey of faith and daily life. In Region V of the Santa Familia Sikumana Parish, the performance of the Head of the Base Community Community (KUB) really determines the quality of pastoral care. This research aims to analyze the relationship between the performance of the KUB Chair and the quality of pastoral care in the region. The method used is quantitative with a correlational design to identify relationships between variables. Data collection was carried out through a survey of 106 heads of families who represented the research population. Data were analyzed using descriptive and inferential statistical techniques such as Pearson correlation tests, linear regression analysis, and validity and reliability tests. The research results show that there is a positive and significant relationship between the performance of the KUB Chair and the quality of pastoral care. The coefficient of determination of 56.6% shows that the performance of the KUB Chair contributes significantly to the quality of pastoral care, while 43.4% is influenced by other factors. Research also finds that indicators such as goals, standards, and feedback have a strong influence on the quality of pastoral care. In conclusion, the performance of the KUB Chair plays an important role in improving the quality of pastoral care. Increasing communication, motivation and understanding of the responsibilities of the KUB Chair are very necessary to optimize services to the people. This research recommends strengthening the capacity of the KUB Chair and the active participation of the congregation to support the success of pastoral services.